Brussels : Body Speech. - De Wolf, Hans M.; Xi, Sydnee Chen; Han, Liu Cody; Duanmu, Doris; Minsheng Art Museum, Shanghai ([S.l.] : [s.n.], 2010)
De Keersmaeker, Anne Teresa ; Claerbout, David ; Tuerlinckx, Joëlle ; Theys, Frank ; Janssens, Ann Veronica
Brussels Body Speech, Minsheng Art Museum, Shanghai, 19.09>07.10 2010
kunstcatalogus
Keywords: De Keersmaeker, Anne Teresa; Claerbout, David; Tuerlinckx, Joëlle; Theys, Frank; Janssens, Ann Veronica